Glecaprevir-Pibrentasvir (Maviret) - CDA-AMC (Canadian Journal of Health Technologies, 2026)
Canada’s Drug Agency (CDA-AMC) recommends that Maviret be reimbursed by public drug plans for acute hepatitis C virus (HCV) infection in adults and in pediatric patients aged 3 years and older and weighing 12 kg or more, if certain conditions are met. The Canadian Drug Expert Committee (CDEC) determined that it is uncertain whether Maviret demonstrates acceptable clinical value in patients with acute HCV infection. Evidence from a clinical trial showed that Maviret given for 8 weeks led to high treatment response and no failure or relapse after treatment in adults with acute HCV infection. However, because the treatment was not compared with anything else, the evidence is very uncertain. There were other uncertainties in the evidence, such as the proportion of patients who would have had a spontaneous resolution if they did not receive Maviret. However, clinical experts considered the results to be strong evidence of drug efficacy because the rate of HCV clearance 12 weeks after the last dose of treatment was much higher than what would be expected without treatment. They also noted that the harms were consistent with the use of Maviret in chronic HCV infection. CDEC considered that there is a significant unmet clinical need for patients with acute HCV infection and for the broader population at risk of contagion. Currently, there is no reimbursed on-label treatment of acute HCV infection, and people are asked to wait until chronic HCV infection develops before accessing treatment. A patient’s health can be affected because progression to a chronic infection can lead to liver disease, which is associated with mortality and can be debilitating. Also, the wait enables transmission of the virus to others at a time when the condition is more contagious. The committee noted that there are ethical and practical challenges with comparative trials that do not treat some patients and thus delay a potential cure, which means that trials are unlikely to be conducted in this fashion. Based on these considerations, CDEC concluded that Maviret may address the significant unmet need to a degree that justifies a positive recommendation despite the uncertainty in the clinical value. Maviret should only be reimbursed for adults with acute HCV infection and for pediatric patients aged 3 years and older and weighing 12 kg or more with acute HCV infection, in line with the Health Canada indication. Maviret should only be covered for patients with a positive HCV ribonucleic acid (RNA) test and who have not received treatment for the current HCV infection. It should only be initiated for 8 weeks. Maviret should only be reimbursed if it is prescribed by a clinician with experience in the diagnosis and management of HCV infection, it is not used in combination with any other antiviral for the treatment of HCV, and the per-course cost of Maviret does not exceed the per-course cost of the least costly direct-acting antiviral reimbursed for chronic HCV infection. Important budget impact considerations must be addressed for health systems to be able to adopt Maviret.